P–666 Validating the hypo-androgenic PCOS-like phenotype (H-PCOS), derived from the "lean" PCOS phenotype at younger ages. (6th August 2021) - Darmon, S; Molinari, E; Albertini, D F; Patrizio, P; Barad, D H; Gleicher, N
Abstract: Study question: Is the resistance to standard infertility treatments of the H-PCOS-like phenotype reversed through reconstitution of androgen levels and can principle diagnostic markers of H-PCOS be validated? Summary answer: Pre-supplementation with dehydroepiandrosterone (DHEA) eliminated treatment resistance of H-PCOS in comparison to matched infertile controls, also validating previously reported diagnostic features of this condition. What is known already: H-PCOS evolves at older ages from a hyper-androgenic "lean" PCOS phenotype at young ages. Its ontogeny diverts from other PCOS phenotype between 20s and mid–30s by going from being hyper- to being hypo-androgenic due to insufficiency in adrenal androgen production, believed to represent an autoimmune process. In contrast to other PCOS phenotypes, the "lean" PCOS phenotype appears highly treatment resistant to standard fertility treatments. Study design, size, duration: Retrospective case control study. Participants/materials, setting, methods: We investigated 54 H-PCOS patients with qualifying diagnostic criteria1, 2 and 50 matched infertility patients without diagnostic H-PCOS criteria as controls. Both study groups underwent routine in vitro fertilization (IVF) cycles, including androgen pre-supplementation in both groups via dehydroepiandrosterone (DHEA) for women diagnosed as hypo-androgenic. Main outcome measures were clinical pregnancy and live birth rates. 1Gleicher et al., J Sterodi Biochem Mol Biol 2017;167:144–152; 2Gleicher N, et al., Endocrine 2018;59(3):661–676 Main results and the role of chance: Study groups were similar in age, number of prior IVF cycles and previous live births. H-PCOS patients in contrast to controls, however, demonstrated previously reported characteristics of H-PCOS diagnosis, including a significantly higher DHEA/DHEAS ratio, significantly higher AMH, confirming higher functional ovarian reserve, significantly lower free testosterone and significantly higher sex hormone binding globulin (SHBG), further confirming lower androgens. Finally, H-PCOS patients also demonstrated significantly increased evidence for immune system hyperactivity. Clinical pregnancy and live birth rates were separately assessed in first IVF cycles and cumulatively. Both analyses demonstrated, even after age-adjustments, absolutely no outcome differences in cycle cancellations, numbers of oocytes retrieved, first and cumulative pregnancy and live birth rates. At least one pregnancy was achieved in 12 women in both groups (22.2% and 24.0%) and at least one live birth in 11 (20.4%) vs. 8 (14.8%), respectively. Limitations, reasons for caution: As a retrospective case control study, here presented data must be interpreted with caution. The close match between H-PCOS and control patients and the very clear differentiation in patient characteristics between the two groups, however, support the credibility of this study. Wider implications of the findings: This study demonstrated that androgen reconstitution in H-PCOS patients completely reversed treatment resistance compared to well-matched infertile control patients. It also validated previously defined diagnostic criteria of H-PCOS, hopefully facilitating a timelier diagnosis of a, still, widely overlooked condition in female infertility. Trial registration number: NA